2020
DOI: 10.1155/2020/1714352
|View full text |Cite
|
Sign up to set email alerts
|

CpG-Oligodeoxynucleotides Alleviate Tert-Butyl Hydroperoxide-Induced Macrophage Apoptosis by Regulating Mitochondrial Function and Suppressing ROS Production

Abstract: Oxidative stress and mitochondrial dysfunction are related to disease pathogenesis. Oligodeoxynucleotide containing CpG motifs (CpG ODN) demonstrate possibilities for immunotherapy applications. The aim of the present work is to explore the underlying mechanism of the cytoprotective function of CpG ODN by employing the oxidative stress modulation in immune cells. We used the imaging flow cytometry to demonstrate that tert-butyl hydroperoxide (t-BHP) induces mitochondrial-mediated apoptosis and ROS production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Furthermore, CpG ODN-mediated TLR9 activation in hepatocyte protects acetaldehyde-induced oxidative stress, mitochondrial dysfunction, and cell death. Consistent with our results, CpG ODN-mediated TLR9 activation protects tert-butyl hydroperoxide-induced mitochondrial dysfunction, oxidative stress, and cell injury in macrophages ( Qu et al, 2020 ). Similarly, CpG ODN-mediated TLR9 signaling prevents shock-mediated death ( Kim et al, 2008 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, CpG ODN-mediated TLR9 activation in hepatocyte protects acetaldehyde-induced oxidative stress, mitochondrial dysfunction, and cell death. Consistent with our results, CpG ODN-mediated TLR9 activation protects tert-butyl hydroperoxide-induced mitochondrial dysfunction, oxidative stress, and cell injury in macrophages ( Qu et al, 2020 ). Similarly, CpG ODN-mediated TLR9 signaling prevents shock-mediated death ( Kim et al, 2008 ).…”
Section: Discussionsupporting
confidence: 90%
“…TLR9, which shows affinity toward both pathogen-derived and endogenous host DNA, is considered to play a crucial role in both DMAPs/PAMPs-induced liver injury by causing neutrophils activation and inflammatory cytokine/chemokine release in ALD ( Roh et al, 2015 ). However, a previous study demonstrated that TLR9 signaling activation protects tert-Butyl hydroperoxide-mediated oxidative stress and cell death in macrophages ( Qu et al, 2020 ). Furthermore, the whole body lack of TLR9 exacerbated diet-induced insulin resistance and obesity in mice ( Hong et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial DAMPs have been identi ed as important mediators of the innate immune response and are implicated in various degenerative conditions [31]. The mitochondria are evolutionary endosymbionts that were derived from bacteria [32], with which they share numerous similarities, including signi cant amounts of unmethylated CpG motifs in their genomes, which also encode essential protein subunits of the oxidative phosphorylation system [33]. Recent studies have shown that mtDNA is recognized by some important pattern recognition receptors (PRRs) of the innate immune system, TLR9, cytosolic in ammasomes, and type I interferon [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic cleavage of PARP by caspase-3 is considered to be a performer of cellular apoptosis [33] . It has been reported that t-BHP treatment increased cleaved-PARP and cleaved-caspase-3 expression [34] . In this study, we found that 7,8-DHF exhibited cellular protective potential via inhibiting the apoptosis protein (cleaved-caspase-3 and cleaved PARP) activation against t-BHP-induced oxidative stress, but 7-HF displayed weak inhibitory effect on the cleaved-PARP and cleaved-casapase-3 expression levels (Figure 10).…”
Section: -Dhf On Apoptosis Protein Expressionmentioning
confidence: 94%